Tingkat Kebugaran Jasmani Siswa SMP Negeri Se-Kecamatan Bosar Maligas Kabupaten Simalungun Provinsi Sumatera Utara - Sabaruddin Yunis Bangun (Journal of Sport Science and Education, 2019)
This research is motivated by the absence of data showing the level of physicalfitness of state junior high school students and there has never been a test to measure the level of physical fitness of students of the State Junior High Schoolin Bosar Maligas District, Simalungun Regency. This study aims to determine the level of physical fitness of students of the State Middle School in Bosar Maligas District, Simalungun Regency. This research is quantitative descriptive.Data collection techniques used are tests and measurements. The population inthis study were all students of the State Middle School of Bosar Maligas Districtwith a total of 646 students. The sample in this study were students of the StateJunior High School of Bosar Maligas District with a total of 120 students taken20% of the total population. The instrument used in this study was by testing the multistage fitness test run test. The data analysis technique used is percentage descriptive analysis. Classified research data shows that the level of physical fitness of students who are in a very poor classification is 109 students (90.83%), 8 students (6.67%) classification is lacking, 3 students (2.5%) are quite good categories and 0 students (0%) classified as good, very good or special. It can be concluded that the level of physical fitness of the students of the State Junior High School in the Bosar Maligas District of Simalungun Regency is in the very less category.